Study of Optic Nerve Sheath Diameter in Normal Nepalese Adults Using Ultrasound - KC, Bidur; Thapa, Amit (Birat Journal of Health Sciences, 2018)
Introduction: Though invasive intracranial devices are gold standard to calculate intracranial pressure (ICP); these are not without any complications. Non-invasive measurement of ICP by Ultrasonography could be a safe and portable technique. Objectives: The objective of the study was to measure and compare values of optic nerve sheath diameter of both eyes in healthy Nepalese adults. Methodology: A prospective cross-sectional study of healthy adult Nepalese volunteers was performed using a 7.5 MHz linear Ultrasound probe on the closed eyelids; optic nerve sheath diameter (ONSD) was measured 3 mm behind the globe in each eye. Results: Optic nerve sheath diameter (ONSD) of both eyes was measured in 100 healthy volunteers of age ranged from 15 to 75 years with a mean of 30.21 ± 14.05 years. There were 18 (18%) male and 82 (82%) female. ONSD for right eye ranged from 3.20 to 4.90 mm with mean of 4.10 ± 0.50 mm and left eye from 3.20 to 4.80 mm with mean of 4.22 ± 0.49 mm. P value for right and left eye ONSD (P = 0.06) and male and female (P = 0.12 and 0.85 for right and left ONSD respectively) were within normal limits. ONSD has no correlation with age (P = 0.27 and 0.27 for right and left ONSD respectively). Conclusion Mean of optic nerve sheath diameter (ONSD) is 4.10mm and 4.22 mm for right and left eye respectively. There is no statistical significant difference in mean of ONSD between right and left eye. BJHS 2018;3(1)5 : 357-360